2004
DOI: 10.1243/0954407042580101
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of loss mechanisms in a pushing metal V-belt continuously variable transmission: Part 2: Pulley deflection losses and total torque loss validation

Abstract: The power transmission efficiency of continuously variable transmissions (CVTs) based on the pushing metal belt is acknowledged to be lower than that of discrete ratio alternatives. This tends to negate the potential fuel economy benefits that are obtained by improved engine/load matching with a CVT. This series of three papers details an investigation into the loss mechanisms that occur within the belt drive as a first step to obtaining improvements in efficiency. This second part follows on from an initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…The desired CVT ratio is retained through a thread design of the moving power screw mechanism. Unlike the existing pulley-based CVT with V-belt in the market, continuous engine power is required to maintain a constant CVT ratio and this is one of the main reasons that reduces the efficiency of CVT [1,16]. As a result, in EMDAP (a)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The desired CVT ratio is retained through a thread design of the moving power screw mechanism. Unlike the existing pulley-based CVT with V-belt in the market, continuous engine power is required to maintain a constant CVT ratio and this is one of the main reasons that reduces the efficiency of CVT [1,16]. As a result, in EMDAP (a)…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the V-belt's misalignment is inevitable in the existing pulley-based CVT with a single-acting pulley system. Studies by some previous researchers suggest that V-belt misalignment causes sinusoidal stresses and transverse forces on the V-belt's band and elements respectively, which reduces the efficiency of (a) (b) (c) the CVT while at the same time also decreasing the lifespan of the V-belt [7,8,16]. With the dual-acting pulley system of EMDAP CVT, the misalignment of the V-belt is reduced significantly; hence the efficiency of the CVT and the lifespan of the V-belt can be increased.…”
Section: Resultsmentioning
confidence: 99%
“…(42), which was based on the average values of CVT torque losses. Previous studies [3][4][5]14] have shown that the efficiency of metal belt CVT can be expressed as a function of ratio and input torque, which is expressed as η = η(i,T in ). The CVT efficiency map that changes with ratio and input torque at η p = 2000 r/min is shown in Figure 5…”
Section: Bench Test Performance and Cvt Efficiency Calculationmentioning
confidence: 99%
“…Numerous studies on the efficiency of CVT and gearbox have been conducted through bench tests in China and abroad. Akehurst et al [3][4][5] used bench tests to study torque losses in a metal belt CVT, which were caused by the relative sliding motion between belt segments and bands. They then forecasted and studied torque losses between belt segments and bands caused by the bending and deformation of the pulley based on experimental observations of pulley deflections.…”
Section: Introductionmentioning
confidence: 99%
“…The power dissipation in the variator is caused mainly by the slip between moving elements, especially between the push-belt and pulley pairs, and secondly by deformations under loaded conditions, especially for the pulleys and pulley sheaves. 24 The slip speed is proportional to the rotational speed of the considered pulley pair, 41 whereas the normal force acting on the slip surface is proportional to the associated clamping force. The deformation force, on the other hand, is proportionally related to the clamping forces of the considered pulley pair, 40 whereas the deformation speed is proportionally related to the associated rotational speed.…”
Section: Parametric Approximationsmentioning
confidence: 99%